Peramalan Produksi Padi Di Provinsi Sumatera Barat dengan Metode LSTM - Yanata, Dwiki Dzakwan; Helma, Helma (Journal of Mathematics UNP, 2025)
The occurrence of rice surplus in West Sumatra Province, makes this province has the potential to become a rice exporting area without reducing local stocks. This research aims to forecast rice production using the LSTM method, which excels in time series data analysis. This research uses secondary data in the form of monthly rice production in West Sumatra from 2009 to 2023 obtained from the Agriculture Office of West Sumatra Province. The process involves data processing, division of the dataset into training and testing data, and construction of the LSTM model. The model is designed to recognize patterns and trends in rice paddy production. The forecasting results show a range of paddy production between 177,038 to 185,343 tons with a MAPE value of 10%, which indicates a good level of accuracy.